Analysis of the Results of Students' Difficulties in Writing News Texts in Grade XI at SMAN 1 Tanjung, North Lombok Regency - Lamusiah, Siti; Almalik, Eza; Aulia, Al-vina; Jannah, Miftahul; Nufus, Hayatun; Sarideti, Desfika; Azhari, Dodi (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to analyze the difficulties experienced by eleventh-grade students of SMAN 1 Tanjung in writing news texts, identify the contributing factors, and describe the quality of writing based on 27 student works. The study used qualitative methods with observation, interview, and documentation techniques. The results showed that most students experienced difficulties in formulating leads, arranging 5W + 1H elements coherently, and applying language rules according to PUEBI. As many as 74% of students were able to write news by fulfilling some criteria, but only 33% fulfilled the criteria well. Factors causing difficulties included minimal experience in writing news, low interest in reading, weak ability to construct effective sentences, and poor spelling mastery. The news topics written by students were divided into two main themes, namely Covid 19 and Technology. The findings of this study underscore the importance of continuous practice, structured learning strategies, and habituation to reading journalistic texts to improve news writing skills.